Simple Method for Non Contact Thickness Gauge using Ultrasonic Sensor and Android Smartphone - Anif Jamaluddin; Fita Listiana; Dwi Teguh Rahardjo; Lita Rahmasari; Dewanto Harjunowibowo (Institute of Advanced Engineering and Science, 2015)
The aim of this research is to develop simple method for non contact thickness gauge using ultrasonic sensor and android smartphone. This system is constructed using ultrasonic sensor HY-SRF05, microcontroller ATMEGA328, bluetooth module and android smartphone. Ultrasonic sensor transmits ultrasonic pulses in the form of waves and recieves back the pulses after the waves are reflected by an object. The time duration of ultrasonic between transmition and reception is calculated as distance between sensor and sample. The method of for thickness measurement adhere sample on holder infront of ultrasonic sensor. The Thickness measurement of sample is calculated base on distance beetwen sensor to holder (fixed barrier) and sample to sensor. The zero position of measurement is distance of sensor to holder. The data of thickness is sent via bluetooth and received by the Android application. Android Application uses to display measurement is designed base on MIT App Inventor for Android (AIA) platform. The measurement results show a fairly high degree of accuracy is 99.978%. DOI: http://dx.doi.org/10.11591/telkomnika.v15i1.7187